MFS transporter superfamily: modelling and dynamics - Lee, J (2016)
The aims for this thesis were threefold. First, is it possible to develop a numbering protocol to aid homology modelling, despite the diversity of MFS sequences? Given these methods, apply these to improve the homology model of a putative MFS protein, SV2A. Finally, can Molecular Dynamics (MD) simulations be used to elucidate the transport mechanism in an MFS protein? There are several solved X-ray crystal structures of secondary active transporter MFS proteins, all of which have a core 12 transmembrane (TM) helix fold. Despite this highly conserved fold, the sequence identity between the transporters is low (15 – 25 % identity between structures) and so this provides difficulties when exploring homology modelling of target proteins based on known structures of MFS transporters. To overcome this, exploration of both conservation of amino acid type in multiple sequence alignments (MSAs) and conservation of contacts between helices elucidate 'anchor points' in the structure. This analysis can be used to aid alignment between template and target in homology modelling, such as for SV2A, which is the binding site for an anti-epileptic drug, levetiracetam. The binding site was thought to be in the central cavity of the TM region of the MFS protein and so drug-protein interactions were explored using MD simulations. Finally, MD simulations were conducted on FucP, the X-ray crystal structure of which is solved in an outward open conformation (open to the perplasmic cavity). The aim for this work was to investigate the movement from the outward open state to the occluded state and determine whether there is any effect on placing static hydrogen atoms on two key titrable residues in the central TM cavity, D46 and E135.